(untitled) (TAJ: Journal of Teachers Association, 2009)
A very low dose of leptin (50 ng) was microinjected into the ventro-medial hypothalamus (VMH) of each rat daily once for three days. Food intake and body weight were measured after leptin injections. Microinjection of leptin into the VMH reduced food intake by 33.3 % significantly (P<0.01) during three days of leptin injection compared to the control. Body weight was measured after 24 h, 48 h and 72 h of leptin injection. After 24 h (P<0.01) and 48 h (P<0.05) of leptin injection, body weight was reduced significantly compared to that of rat before injection. Similarly, after 72 h of leptin injection, a significant reduced body weight was observed (P<0.1). A significant (P<0.001) reduced changes of body weight were found after 24 h, 48 h and 72 h after injection into the VMH when compared to the respective controls injected with saline. The results suggest that leptin has dramatic effect on reducing body weight by inhibition of food intake. doi: 10.3329/taj.v19i2.3154 TAJ 2006; 19(2): 70-75